Use of 3D Volume Rendering Based on High-Resolution Computed Tomography Temporal Bone in Patients with Cochlear Implants - Ciodaro, Francesco (Am J Case Rep, 2019)
Case series Patients: Male, 50 • Male, 3 • Female, 55 Final Diagnosis: Malposition of the array Symptoms: Deafness Medication: — Clinical Procedure: Cochlear Implant 3D rendering Specialty: Audiology OBJECTIVE: Challenging differential diagnosis BACKGROUND: The purpose of this study is to demonstrate the advantages of 3D volume rendering in postoperative control of implants placement compared to high-resolution computed tomography (HRCT). CASE REPORT: We describe 3 patients who underwent HRCT study with and without 3D volume rendering after surgery for cochlear implantation. In 2 patients, the traditional HRCT showed a suspected malposition of the array, excluded only by the rendering reconstruction. In the other patient, thanks to the 3D rendering, we were able to identify the complete migration of the array out of the cochlea and the tip of the electrode near the opening of internal auditory canal, while the traditional images showed only that the array was not rolled up inside the cochlea. CONCLUSIONS: HRCT showed complex anatomic structures of the inner ear and contents of the middle ear cavity. The volume rendering, in the postoperative control, generates interactive 3D images of the cochlear implant, facilitating a clearer representation of the topographic complex of the cochlea, giving more detailed diagnostic information than the HRCT.